Mechanical characteristics of herbaceous plant root system and slope stability research - Shilin Tan; Guoping Xiang; Xiangning Xu; Tao Liu (Scientific Reports)
Abstract It is of great significance to study the mechanical properties of plant roots and root-soil interactions on the effect of root consolidation. In order to study the mechanical effects of herbaceous plant root systems on the slopes of the Haizhou open-pit mine, Medicagosativa L.( Species 1), Iris lactea Pall. var.chinensis (Fisch.) Koidz.( Species 2), and Euphorbia hypericifolia L.( Species 3) were taken as the research objects to carry out indoor root tensile tests, in situ shear tests, quantitatively calculated the additional cohesive force of the root system with Wu and FBM models, compare the applicability of the two models, and the Wu model was modified to compare the soil consolidation effects of different plant root systems; A simplified slope numerical model was used to investigate the shallow damage protection effect of rooted slopes with the same root area ratio. The results showed that (1) the tensile strength of the root systems of the three herbaceous plants increased with the root diameter in a power function relationship, and the tensile strength decreased with the root diameter in a power function relationship; (2) The Wu modification coefficients of Species 1, Species 2, and Species 3 were 0.17, 0.15, and 0.58, respectively. Comparing the modification coefficients of the three herbaceous plants, Species 3 had the largest modification coefficients; Species 1 was the second largest, and Species 2 had the smallest modification coefficients; the actual increment in cohesive force was close to that in the FBM model, and the FBM model was significantly better than the Wu model; (3) The mechanical and morphological properties of Species 3 made its root system consolidation effect the greatest compared with Species 1 and Species 2 root-soil interaction.